Integrating Numeracy and Literacy Across the Curriculum: Challenges Encountered by Elementary Teachers of Osmeña Colleges in Promoting 21st-Century Skills, Personal Qualities, and Learner Competencies - Mostoles, Rosario (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the challenges encountered by elementary teachers of Osmeña Colleges in integrating numeracy and literacy across the curriculum to promote 21st-century skills, personal qualities, and learner competencies. Anchored on Constructivist Learning Theory, Curriculum Theory, and Multiple Intelligences Theory, the study explored how interdisciplinary instruction supports holistic learner development while identifying barriers affecting implementation. The study utilized a descriptive-quantitative research design and employed a structured questionnaire-rating scale as the primary data-gathering instrument. Fourteen elementary teachers from Osmeña Colleges during the Academic Year 2023–2024 participated in the study through census sampling. Data were analyzed using percentage distribution and weighted mean. Findings revealed that most respondents were early- to mid-career professionals with moderate teaching experience and predominantly held Bachelor’s Degrees. Teachers encountered moderate challenges in integrating numeracy and literacy, particularly in aligning literacy skills with Science and Mathematics subjects. Other identified barriers included limited instructional materials, curriculum rigidity, inadequate training, and insufficient institutional support. Despite these constraints, teachers demonstrated positive use of adaptive instructional strategies such as differentiated instruction, project-based learning, and real-life contextualized tasks to promote learner competencies and 21st-century skills. However, collaborative and thematic teaching approaches remained underutilized. Institutional support mechanisms were perceived as limited, especially regarding budget allocation, policy frameworks, and resource provision for interdisciplinary projects. The study concluded that successful curriculum integration requires targeted professional development, structured curriculum alignment, stronger institutional support, and sustainable policy implementation. Recommendations focused on strengthening interdisciplinary pedagogy, collaborative curriculum planning, professional recognition systems, external partnerships, and long-term curriculum development initiatives. This study supports Sustainable Development Goal (SDG) 4: Quality Education by promoting inclusive and effective teaching practices that enhance literacy, numeracy, and 21st-century competencies among learners. It also aligns with SDG 17: Partnerships for the Goals through its emphasis on institutional collaboration and external support systems for educational improvement. The sustainability impact of the study lies in its potential to strengthen institutional instructional practices, improve teacher capacity, and support long-term curriculum innovation in private elementary education.
Keywords: 21st-Century Skills; Curriculum Integration; Differentiated Instruction; Elementary Teachers; Institutional Support; Interdisciplinary Instruction; Learner Competencies; Literacy; Numeracy; Professional Development